QUALITY ASSESSMENT OF ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION WITHOUT CONCOMITANT CARDIOVASCULAR DISEASES AS A PART OF OUTPATIENT RECVASA REGISTER - A. V. Zagrebelnyy; S. Yu. Martsevich; M. M. Loukianov; E. A. Pravkina; A. N. Vorobyev; S. S. Yakushin; S. A. Boytsov (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To assess the quality of arterial hypertension (HT) pharmacotherapy within the outpatient register RECVASA, emphasizing whether the choice of antihypertensive drugs (AHD) is in line with current clinical guidelines.Material and methods. Patients with HT without ischemic heart disease, chronic heart failure and atrial fibrillation (n=741) were selected from all patients (n=3690) included into the register. Among concomitant diseases were revealed the following: bronchial asthma and/or chronic obstructive pulmonary disease (COPD) – in 42 (5.7%) patients; obesity – in 93 patients, impaired glucose tolerance – in 9 patients, and diabetes mellitus – 84 patients. Prescription of AHD, their number and class were recorded at every next visit to doctor. Accuracy of AHD choice, compliance with current clinical guidelines, and other considerations were assessed through the example of beta-blockers (BBs).Results. AHD were prescribed to 641 patients, and in 13.5% of patients did not receive any AHD. 49.7% of patients received ACE inhibitors, 38.5% – diuretics, 32.5% – BBs. BBs were prescribed to the third part of patients with diabetes and obesity. Furthermore a quarter patients with COPD and the third part of patients with bronchial asthma received BBs. BBs in combination with thiazide diuretics were prescribed to 12 (41.4%) patients with diabetes mellitus and to 13 (40.6%) patients with obesity.Conclusion. Doctors do not always make AHD choice according to current clinical guidelines. Compliance of AHD choice with current clinical guidelines should be an element of treatment quality assessment.